Global Sustainable Development: Ideological and Political Education-Based Theoretical Deconstruction and Practical Paths - Hu, Dandan; Li, Xinrui; Chen, Yue (INTI International University, 2025)
This project takes ideological and political education as the starting point, combines the global Sustainable Development Goals, analyzes the value foundation and educational paths of sustainable development at the theoretical level, and proposes a practical framework. Through multi - dimensional research methods, it analyzes the core role of ideological and political education in cultivating sustainable development awareness and promoting social actions, constructs a three - dimensional model of “value guidance – knowledge transformation – practical participation”, and builds a scientific basis chain for the transformation of ideological and political education theory into sustainable development practice